Risk Factors for Brain Metastases in Patients with Renal Cell Carcinoma. (9th March 2020) - Ke, Zhi-Bin; Chen, Shao-Hao; Chen, Ye-Hui; Wu, Yu-Peng; Lin, Fei; Xue, Xue-Yi; Zheng, Qing-Shui; Xu, Ning; Wei, Yong
Abstract : Background . Patients with brain metastases (BM) from renal cell carcinoma (RCC) were considered to experience a poor prognosis. However, there is little knowledge on the risk factors for BM from RCC at diagnosis. This study was aimed at exploring the risk factors for patients with BM from RCC and the interaction among these risk factors. Methods . A total of 38759 cases of RCC were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Risk factors for BM from RCC were evaluated by univariate and multivariate logistic regression analyses. Interaction effect between age and tumor size was tested. Results . There was a significant difference in univariate analysis, including T stage, tumor size, grades III and IV, lymph node metastasis, bone metastasis, liver metastasis, lung metastasis, and surgery. There was a significant difference in multivariate analysis, including age, T stage, tumor size < 10 cm, grade IV, lymph node metastasis, bone metastasis, lung metastasis, and surgery. Patients older than 70 had 0.653-fold lower risk of developing BM compared with those younger than 70. Patients with tumor size ≥ 4 cm and <10 cm had higher risk of developing BM compared with those < 4 cm . The larger the tumor size, the higher the incidence of BM from RCC in those whose tumor size was less than 10 cm. An interaction test between the tumor size and age on brain metastasis was statistically significant in the crude analysis (P = 0.0114 ) and model II analysis (P = 0.0248 ) but not in model I analysis (P = 0.1136 ). Although age significantly affected the risk of BM from RCC, impact of age on the risk of developing BM from RCC was limited to patients with tumor size ≥ 7 cm . Conclusion . Both tumor size and age were independent risk factors for brain metastases in patients with RCC. The impact of age on the risk of developing BM from RCC was limited to patients with tumor size ≥ 7 cm . Patients with a larger tumor size and younger age might have the higher risk of developing BM at diagnosis of RCC.